PENGEMBANGAN PASAR LELANG FORWARD KOMODITAS BAHAN OLAH KARET (BOKAR) DI PROVINSI SUMATERA SELATAN - Heri Rahman (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2015)
World rubber demand increased continuously in line with the increase in global rubber industry needsfor the countries like US, Japan, Europe, and China. The potential and opportunity should boostIndonesia's natural rubber exports, provide to increase the income of farmers that producing MaterialRubber (Bokar), indirectly. However, the lack of reference prices of rubber smallholder at thenational level, made of the farmers always disadvantaged, because the prices tend to be determined bythe traders and manufacturers, and made weak the bargaining position of farmers, so the developmentof forward auction market into the potential and opportunities for Bokar’s sales that can benefit thefarmers. The results showed that the forward auction market of Bokar has the potential andopportunities as a good place for transaction that more profitable for farmers. Through the forwardauction market, the farmers were required to be willing and able to associated, produced good qualityof Bokar, so that the Bokar’s value of sale was higher, because it sold by the association in a auctionway.